2016
DOI: 10.1242/jcs.196162
|View full text |Cite
|
Sign up to set email alerts
|

How cells respond to environmental cues – insights from bio-functionalized substrates

Abstract: Biomimetic materials have long been the (he)art of bioengineering. They usually aim at mimicking in vivo conditions to allow in vitro culture, differentiation and expansion of cells. The past decade has witnessed a considerable amount of progress in soft lithography, bioinspired micro-fabrication and biochemistry, allowing the design of sophisticated and physiologically relevant micro-and nanoenvironments. These systems now provide an exquisite toolbox with which we can control a large set of physicochemical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 168 publications
1
68
0
Order By: Relevance
“…In the body, cells migrate through the extracellular matrix, whose microstructure defines physical boundary conditions for various vital cell activities, including cell migration. It is well established that cell migration is influenced by topographical cues from the environment . In vitro experiments using protein tracks and micro‐/nano‐fabricated grooves and ridges have convincingly demonstrated that the migration of adherent cells is guided by anisotropic topographical features (i.e., structures with different geometric properties in different directions) of the substrate—a phenomenon termed “contact guidance.” Such studies have yielded important insights into the fundamental mechanisms underlying cell migration, which contribute toward our understanding of morphogenesis and disease development, such as in cancer metastasis .…”
Section: Introductionmentioning
confidence: 99%
“…In the body, cells migrate through the extracellular matrix, whose microstructure defines physical boundary conditions for various vital cell activities, including cell migration. It is well established that cell migration is influenced by topographical cues from the environment . In vitro experiments using protein tracks and micro‐/nano‐fabricated grooves and ridges have convincingly demonstrated that the migration of adherent cells is guided by anisotropic topographical features (i.e., structures with different geometric properties in different directions) of the substrate—a phenomenon termed “contact guidance.” Such studies have yielded important insights into the fundamental mechanisms underlying cell migration, which contribute toward our understanding of morphogenesis and disease development, such as in cancer metastasis .…”
Section: Introductionmentioning
confidence: 99%
“…Cells can reorganize and re-engineer their environments through mechanical and biochemical interaction with the substrate. Therefore, cells can strongly in uence the hydrogel matrices in which they are embedded, in the short term through interaction with the crosslinking mechanism and long-term through remodeling [78][79][80]. Weihua et al demonstrated that Bortezomib, an FDA-approved small molecule for the treatment of myeloma, inhibits the expression of MMP-13, leading to a reduction of collagen type 2 degradation [82].…”
Section: Discussionmentioning
confidence: 99%
“…Both materials (SA and PVA) are known to be biocompatible, biodegradable and good for the cells [67,68]. However, it is known that cells are able to sense the environment [69] and in addition to the material properties (internal chemical composition and the mechanical properties) [70], the material surface modification may change the behavior of the cells [71,72]. The overall idea of using surface modified structures is to stimulate the cells or their behavior.…”
Section: Safety Of Bi-layered Carriers and The Effect Of Surface Modimentioning
confidence: 99%